PENGARUH INDEPENDENSI, KOMPETENSI, DAN LOVE OF MONEY PADA KINERJA PEMERIKSA INSPEKTORAT KABUPATEN GIANYAR - Syantika, I Wayan; Mimba, Ni Putu Sri Harta; Budiasih, IGA Nyoman (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.03.TAHUN 2017, 2017)
This study is aimed to determine the effect of independence, human resource competences, and love of money on the performance  of intern government examiners(i.e. inspectorates)  in Gianyar regency. This study involved the entire examiners by using method of survey  and primary data that obtained from questionnares, using census for data collection technique. The number of respondents in this research is 37 people. Data analysis method used is multiple linear regression which was preceded by the test of validity and reliability as well as the classical assumption test.The results of this study indicate that the performance  of  intern government examiners is positively affected by independence, and human resource competences.  In addition the performance of Inspectorate in Gianyar Regency is negatively affected by love of money .
Keywords: independence, competence, love of money, the performance